Identification of factors to reduce the energy costs of dispersing in jets - Gorobets, Larisa; Verkhorobina, Inna; Biletsky, Volodymyr; Kryvenko, Andrii; Hryshchenko, Mykhailo; Bulakh, Oleksij (Eastern-European Journal of Enterprise Technologies, 2020)
This paper reports the operational indicators for industrial-sized jet grinding plants (JGP). The dependences of specific energy consumption on productivity have been generalized. The technological patterns in the working process were considered in terms of reducing energy costs using the operation of gas-jet and steam-jet mills at the Vilnohirsk Mining and Metallurgical Plant (VMMP) involved in crushing zircon to 60 µm as an example. The acoustic activity in the grinding area has been studied relative to the concentration of μ and in combination with the technological assessment of the mill’s performance. A broadband piezo sensor was used in the assessment of acoustic emission (AE). It is shown that the acoustic activity of the grinding zone contains information about the effects of dispersion and energy costs for grinding, which makes it possible to estimate and minimize the specific energy costs. It has been established that the principal factors of JGP energy intensity are the initial temperature of the energy carrier, which sets the speed of the jet, and the concentration of solid phase in the jet, which changes the effects of dispersing. A technique has been proposed for the current assessment of energy costs in the working process of dispersion based on the experimental acoustic data and a pattern of the acoustic dimensional effect. The estimated acoustic indicators of the energy cost of a jet mill for the conditions of VMMP were derived. To reduce the energy cost of dispersion (γs@0.42 J/cm2), the effect of adjusting the loading of jets to γN@1.8 J/pulse is employed. Thus, this study has investigated the dispersal of solid loose material in jets with the involvement of acoustic information about the operation of jet mills, which makes it possible to comprehensively assess and minimize (optimize) the specific energy costs of grinding